1986
DOI: 10.1128/jvi.57.2.638-646.1986
|View full text |Cite
|
Sign up to set email alerts
|

Guanidine-selected mutants of poliovirus: mapping of point mutations to polypeptide 2C

Abstract: Sequence analysis of the genomic RNA of interstrain guanidine-resistant and antibody-resistant variant recombinants of poliovirus type 1 mapped the resisti4nce of mutants capable of growth in 2.0 mM guanidine hydrochloride to a region located 3' of nucleotide 4444. This region of the viral genome specifies the nonstructural protein 2C. The sequence of genomic RNA encoding 2C from six independently isolated mutants resistant to 2.0 mM guanidine was determined. All six isolates contained a mutation in 2C at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(91 citation statements)
references
References 51 publications
6
83
1
1
Order By: Relevance
“…GuHCl inhibits the NTPase and RNA helix-unwinding activities of NV NS3. Previous studies have reported that the NTPase and RNA helicase activities of enterovirus 2C ATPase can be inhibited by GuHCl (22,(41)(42)(43)(44)(45), which also inhibits replication of the vRNAs of a number of enteroviruses (46,47). Given the similarity between the consensus motifs in enterovirus 2C ATPase and norovirus NS3, we wanted to examine whether NV NS3 could also be a target for guanidine inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GuHCl inhibits the NTPase and RNA helix-unwinding activities of NV NS3. Previous studies have reported that the NTPase and RNA helicase activities of enterovirus 2C ATPase can be inhibited by GuHCl (22,(41)(42)(43)(44)(45), which also inhibits replication of the vRNAs of a number of enteroviruses (46,47). Given the similarity between the consensus motifs in enterovirus 2C ATPase and norovirus NS3, we wanted to examine whether NV NS3 could also be a target for guanidine inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Virus-encoded RNA-remodeling proteins, particularly helicases, have long been considered valuable targets for antiviral compounds, because they are well conserved within or even across virus families (57). In particular, enterovirus 2C ATPase , another SF3 viral RNA helicase, has been found to be inhibited by ϳ1 mM GuHCl, as is enterovirus replication (22,(42)(43)(44)(45). Using an NV replicon as a model, our studies demonstrated that ϳ1 mM GuHCl can significantly inhibit the replication of HuNoV in cultured human cells with negligible cell toxicity ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is in agreement with the available experimental data implicating these proteins in viral RNA replication and with the reported NTP-binding capacity of TMV p126 (Evans et al 1985), although direct testing is certainly warranted. In fact, there is experimental evidence that clearly, though indirectly, demonstrates the importance of the NTP-motif in viral RNA replication, Recently several poliovirus mutants resistant to or dependent on guanidine, a potent inhibitor of RNA replication of some picornaviruses, have been thoroughly studied (Pincus et al 1986(Pincus et al , 1987. They all mapped to the 2C protein, with the amino acid replacements located in the proximity of the "A" and "B" sites of the NTPmotif, or near the conserved Asn residue in the 183rd position of the segments of 2C aligned in this paper (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The above-mentioned guanidine-resistant (g r ) poliovirus mutants are a typical example. The drug targets the viral multifunctional protein 2C (414)(415)(416)(417)(418), which possesses an RNA-dependent NTPase activity (419,420) and, in particular, is hypothesized (though not proved) to function as an RNA helicase (421)(422)(423). Both g r and guanidine-dependent (g d ) classes of mutants display a wide range of phenotypes with different levels of dependence of reproductive efficiency on the guanidine concentration (416,424).…”
Section: Development Of Resistance To Mutagenic and Some Other Inhibimentioning
confidence: 99%